(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يتلخص هذا البحث في مجموعة نقاط أساسية تعريفية أولاً ، ثانياً العولمة بوصفها نتاج قوة ذاتية تحافظ على دائرة استمرارها كما يوجد في هذا البحث الجانب الشمولي للعولمة في العلاقات الاندماجية المعقدة بين البشر على المستوى الفردي والثقافي والمؤسسي الاجتماعي، كما ركزت على نقطتين هامتين الأولى أن حركة العولمة هي محاولة لجمع دول العالم ومناطقها المختلفة في كيان واحد وهذا ما عرف بالقرية الصغيرة، أما النقطة الثانية فحاولت فيها التركيز على أبعاد العولمة و وعينا بحدوثها لأن هذه الحركة تؤدي إلى انخراطنا في دولة أطلقوا عليها المجتمع العالمي. IN this research,I have First defined many issues, then I have tried to explain globalization being the out come of a self power , including its continuation. I have also shed light on the comprehensive side of globalization through the complex inter relation among human Beings on the cultural , individual , institutional and social level. I have tried to focus on two main points. First, Globalization is an attempt to gather the world states and their different regions in one entity , This is known as a small village. Second, I have focused on the dimensions of globalization and our awarcness of it , because this movement makes us engaged in one state , called "the global society" .